92.2k views
2 votes
Enter the value of n so that the expression (ny + 25.7) + (–45.2y + 13.9) is equivalent to (–33.7y + 39.6).

1 Answer

3 votes

Answer:


n=11.5

Explanation:

we have


(ny+25.7)+(-45.2y+13.9)=(-33.7y+39.6)

Group terms than contain the same variable in the left side of the equation


(ny-45.2y)+(25.7+13.9)=(-33.7y+39.6)

Combine like terms in the left side


(ny-45.2y)+(39.6)=(-33.7y+39.6)

Simplify


ny-45.2y=-33.7y


ny=-33.7y+45.2


ny=11.5y

Simplify the y


n=11.5

User Shivkumar Kondi
by
5.5k points